(untitled) (Eurasian Journal of Research, Development and Innovation, 2022)
From the moment our country gained independence, the processing of oil raw materials produced in our country has become an acute problem. In this regard, the construction of an oil refinery in Bukhara ready to process these raw materials into a finished product was a priority task. As we can already see from the example of this plant, our country coped with this task perfectly. The plant’s products are widely used in many sectors of agriculture in our state. And this, in turn, strengthens the economy of Uzbekistan